2013
DOI: 10.1371/journal.pone.0080586
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Organized Dynamical States in Chemical Oscillator Networks: Synchronization, Dynamical Differentiation, and Chimera Patterns

Abstract: Dynamical processes in many engineered and living systems take place on complex networks of discrete dynamical units. We present laboratory experiments with a networked chemical system of nickel electrodissolution in which synchronization patterns are recorded in systems with smooth periodic, relaxation periodic, and chaotic oscillators organized in networks composed of up to twenty dynamical units and 140 connections. The reaction system formed domains of synchronization patterns that are strongly affected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
174
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 218 publications
(179 citation statements)
references
References 47 publications
1
174
4
Order By: Relevance
“…First found in identical and symmetrically coupled phase oscillators [2], chimera states have been the focus of extensive research for over a decade now. Both theoretical and experimental works have shown that this counter-intuitive collective phenomenon may arise in numerous systems including mechanical, chemical, electro-chemical, electrooptical, electronic, and superconducting coupled oscillators [3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…First found in identical and symmetrically coupled phase oscillators [2], chimera states have been the focus of extensive research for over a decade now. Both theoretical and experimental works have shown that this counter-intuitive collective phenomenon may arise in numerous systems including mechanical, chemical, electro-chemical, electrooptical, electronic, and superconducting coupled oscillators [3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in a purely mechanical experiment involving two groups of identical metronomes, it was shown that chimeras emerge naturally as a coexistence of two competing synchronization patterns [25]. Chimeras were also realized in experiments involving electronic nonlinear oscillators with delay [26] and electrochemical oscillator systems [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…This so-called chimera state is counter-intuitive as it appears even when the oscillators are identical, but, since its discover, this state has become a relevant subject of investigation for experimental and theoretical scientists active in different fields ranging from laser dynamics to chemical oscillators, from mechanical pendula to (computational) neuroscience. In particular chimera states have been shown to emerge in various numerical/theoretical studies [26][27][28][29][30][31][32][33][34][35] and in various experimental settings, including mechanical [36][37][38], (electro-)chemical [39][40][41] lasing systems [42,43] and BOLD fMRI signals detection during resting state activity [44], among others. Therefore chimera states are an ubiquitous phenomenon in nature much like synchronization itself and may often have been overlooked or dismissed in previous studies.…”
Section: Introductionmentioning
confidence: 99%